Bioretention system mediated by different dry–wet alterations on nitrogen removal: Performance, fate, and microbial community - Chen, Yao; Chen, Renyu; Liu, Zhen; Ren, Bangxing; Wu, Qiong; Zhang, Jian; Tang, Yinghui; Wu, Qingyu (The Science of the total environment, 2022)
In laboratory experiments, the nitrogen migration and transformation in the stormwater bioretention system under different dry–wet alterations were studied. The removal efficiency showed that nitrogen could be removed efficiently in bioretention system under all dry–wet alterations, and the shorter antecedent dry days (ADDs) (1–5 days) were beneficial to the removal of nitrogen before plants decay, compared to the longer ADDs (7–22 days). Using a new method combined with Hydrus-1D model, water transport was simulated and nitrogen migration in bioretention system was quantified, indicating that NH4+-N was mainly removed in the planting layer, and the removal of NO3−-N was occurred in the submerged layer. Fate experiment showed the main fate of the nitrogen was microorganisms (1–5 ADDs) and soil immobilization (7–22 ADDs). Microbial analysis showed that shorter ADDs (1–5 days) were suitable for Firmicutes growth, while Proteobacteria and Actinobacteria accounted for greater abundance under longer ADDs (7–22 days). Canonical correlation analysis (CCA) revealed the relationships between microbial community and environmental factors. Soil moisture content, soil organic matter (SOM), TN (water), root length, and NO3−-N (water) were significantly correlated with bacterial community. This work may give new insights into nitrogen migration and transformation, and can provide a reference for the further mechanism study and construction of stormwater bioretention systems. [Display omitted] •The 3–5 ADDs were beneficial to the nitrogen removal in bioretention systems.•The fate of TN was quantitatively investigated in bioretention systems.•Increased ADDs promoted the growth of Proteobacteria and Actinobacteria, while inhibiting Firmicutes.•Combined with the Hydrus-1D model, a new method of quantitative N migration and transformation was proposed.